Cover Feature: Faster Intercalation Pseudocapacitance Enabled by Adjustable Amorphous Titania Where Tunable Isomorphic Architectures Reveal Accelerated Lithium Diffusivity (Batteries & Supercaps 7/2022). Issue 7 (15th June 2022) - van den Bergh, Wessel; Larison, Taylor; Jesus Jara Fornerod, Maximiliano; Guldin, Stefan; Stefik, Morgan
Abstract : The Cover Feature shows a crystal structure being disordered to enable faster energy storage. More information can be found in the Research Article by M. Stefik and co‐workers .